2009
DOI: 10.1128/aem.01674-08
|View full text |Cite
|
Sign up to set email alerts
|

Differential Role of Passerine Birds in Distribution of Borrelia Spirochetes, Based on Data from Ticks Collected from Birds during the Postbreeding Migration Period in Central Europe

Abstract: Borrelia spirochetes in bird-feeding ticks were studied in the Czech Republic. During the postbreeding period (July to September 2005), 1,080 passerine birds infested by 2,240 Ixodes ricinus subadult ticks were examined. Borrelia garinii was detected in 22.2% of the ticks, Borrelia valaisiana was detected in 12.8% of the ticks, Borrelia afzelii was detected in 1.6% of the ticks, and Borrelia burgdorferi sensu stricto was detected in 0.3% of the ticks. After analysis of infections in which the blood meal volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
7
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 35 publications
9
90
7
6
Order By: Relevance
“…was detected in 35% of nymphs removed from birds (Kipp et al 2006). Similar results were reported from Czech Republic (Dubska et al 2009) and Switzerland (Poupon et al 2006), where Borrelia spp. prevalence in birdderived nymphs was 31.4%, and 34.6%, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…was detected in 35% of nymphs removed from birds (Kipp et al 2006). Similar results were reported from Czech Republic (Dubska et al 2009) and Switzerland (Poupon et al 2006), where Borrelia spp. prevalence in birdderived nymphs was 31.4%, and 34.6%, respectively.…”
Section: Discussionsupporting
confidence: 77%
“…This is not the first time that Bo. afzelii has been detected in I. ricinus ticks feeding on birds (5,26,56) and even in larvae (9,37,42). In a study on a bird conservation island in the Baltic Sea, Bo.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in France (93) and England (94) found that introduced species of rodents were infected with the bird-adapted B. garinii. Similarly, other studies found that birds can transmit the rodent-adapted B. afzelii (95,96). Rodents or birds that are coinfected with B. afzelii and B. garinii could transmit both species to feeding ticks.…”
Section: Cross-immunity and Co-occurrence Of Borrelia Ospc Strainsmentioning
confidence: 99%